Rendezvous and coordination in OFDM-based dynamic spectrum access networks - Sutton, Paul (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2008)
This dissertation shows that intentionally embedded cyclostationary signatures provide a robust and flexible technique for overcoming the challenge of network rendezvous and coordination in emerging Dynamic Spectrum Access Networks (DySPANs). Conventional wireless systems operate within fixed frequency ranges and rely upon exclusively-assigned licenses for interference avoidance. In contrast, DySPANs dynamically reconfigure their parameters of operation in order to exploit unused spectrum resources while using an awareness of their environment to avoid the creation of harmful interference. In this way, DySPANs achieve high levels of spectrum use; efficiency and offer a solution to the 'spectrum scarcity' issue being faced by telecommunications regulators around the world.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin